2020
DOI: 10.1021/acs.jpcb.0c02570
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Computational Predictions and Experimental Results for Aluminum Triflate in Tetrahydrofuran

Abstract: Exploring reliable electrolytes for aluminum ion batteries requires an in-depth understanding of the behavior of aluminum ions in ethereal-organic solvents. Electrolytes comprised of aluminum trifluoromethanesulfonate (Al-triflate) in tetrahydrofuran (THF) were investigated computationally and experimentally. Optimized geometries, redox potentials, and vibrational frequencies of species likely to be present in the electrolyte were calculated by density functional theory and then measured spectroscopically and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 35 publications
(71 reference statements)
8
24
0
Order By: Relevance
“…Moreover, comparing the Al(OTF) 3 /THF spectra to that of pure solvent (THF), we find that the peak at 1068 cm −1 becomes broader as the concentration increases, suggesting that this band is not only associated with THF but also Al − CIP and/or Al-Agg. 63,74 The peak emerging at 883 cm −1 , as supported by our DFT calculations, can be assigned to ν(Al − O) coupled with τCH 2 of Al − THF bond. (See table S1.…”
Section: Resultssupporting
confidence: 69%
See 4 more Smart Citations
“…Moreover, comparing the Al(OTF) 3 /THF spectra to that of pure solvent (THF), we find that the peak at 1068 cm −1 becomes broader as the concentration increases, suggesting that this band is not only associated with THF but also Al − CIP and/or Al-Agg. 63,74 The peak emerging at 883 cm −1 , as supported by our DFT calculations, can be assigned to ν(Al − O) coupled with τCH 2 of Al − THF bond. (See table S1.…”
Section: Resultssupporting
confidence: 69%
“…Density functional theory (DFT) calculations coupled with Fourier transform infrared spectroscopy (FTIR) suggested that Al exists in these solutions as fully solvated Al-complexes, in addition to the presence of innersphere and outer-sphere trifluoromethansulfonate anions (OTF − ). 63 Further investigation at higher concentrations (>0.1M), presented herein, reveals that these solutions are dominated by [Al(THF) 2 (OTF) 2 ] + . The structure evolution of these species is depicted in (Figure 1a-c).…”
Section: Introductionmentioning
confidence: 63%
See 3 more Smart Citations